Legal Protection of Auction Winners of Agraria Disputes of Confiscated Assets through KPKNL - Brilian Moktar; Elfira Fitriyani Pakpahan; Kartina Pakpahan; Ok Isnainul; Tommy Leonard (CSR International Journal, 2021)
It is important to know the rights of the auction winner in every auction procedure. This includes legal protection for the winning bidder for assets confiscated through the State Wealth and Auction Service Office (KPKNL). This research will reveal the legal protection section of agrarian disputes over the auction of bppn confiscated assets through KPKNL in Medan City. Data collection used Normative Juridical review. Research informants only focus on employees and parties who have problems related to the agrarian suspicion of the auction of confiscated assets by the Indonesian Bank Restructuring Agency, confiscate through KPKNL in the Medan branch. The conclusion is that legally the auction, there are inappropriate regulations by the Central KPKNL and the Medan city area. There are also problems with policies made by agraria confiscate, where the regulations are not well integrated. KPKNL has conducted an auction, but has not provided certainty for the auction winner. In this case, the auction winner gets a loss because he has followed all procedures and did not receive what has been stipulated by KPKNL.